Comparison of functional outcomes among subtypes of Fraser’s type Ⅱ floating knee - Deepak Chouhan; Devendra K. Chouhan; Rajendra K. Kanojia; Prateek Behera (Chinese Journal of Traumatology, 2021)
Purpose: The poor prognosis in patients with floating knee injuries is mainly contributed to articular involvement (Fraser’s type Ⅱ). This study aims to evaluate and compare the functional outcomes among different Fraser’s type Ⅱ floating knee injuries after surgical management. Methods: Twenty-seven patients with Fraser’s type Ⅱ floating knee injuries (54 fractures) between September 2014 and December 2015 were enrolled prospectively in this study and were distributed according to Fraser’s floating knee classification into three different groups as type ⅡA (ipsilateral femoral shaft and tibial intra-articular involvement, n = 11), type ⅡB (ipsilateral tibial shaft and femoral intra-articular involvement, n = 9) and type ⅡC (both femoral and tibial intra-articular involvement, n = 7). The differences among the groups were evaluated and compared. The functional outcomes of these injuries at one year were analyzed using Knee Injury and Osteoarthritis Outcome Score (KOOS) which covers 5 subscales of pain, other symptoms, activities of daily living, sports and recreation, and quality of life. The result was also compared with standardized age-sex matched healthy population using paired samples t-test. Results: All the patients were male, and the injury mechanism was solely roadside accident. The mean age was 29.8 years and injury severity score 17.9 (comparable in all the three groups). Most injuries were observed on the right side (20 cases, 74.1%). Based on paired samples t-test, the KOOS score of patients with Fraser’s type ⅡA was found to be better than that of type ⅡB and type ⅡC. Compared with the reference age-sex matched control group, patients with Fraser’s type ⅡB and ⅡC fractures had significantly lower mean score in all KOOS subscales (all p < 0.01). However, Fraser’s type ⅡA only revealed significant difference regarding the subscales of activities of daily living (p < 0.0001), sports and recreation (p < 0.0001), and quality of life (p < 0.0001). Conclusion: The results of this study show that patients with Fraser’s type ⅡA fractures had a better functional outcome as compared to those with type ⅡB and ⅡC fractures. This might be due to the open intra-articular involvement of the distal femur of the latter two fracture types.